Berufliche Qualifizierung und Qualifikationsverwertung in Japan - Demes, Helmut [Verfasser]; Georg, Walter [Verfasser] (My University, 1997)
This paper outlines the relationship between education, vocational training, work organization and individual careers in Japan, focusing on the segment of blue collar work. Public vocational training is not well developed and each private enterprise trains its own employees according to its own standards and needs. The return of investment is secured by long-term employment in internal labour markets. Employers prefer new graduates from the education system, putting emphasis on recruitment criteria, such as academic achievement, general knowledge and social competence but not on vocational skills. This educational-meritocracy is, however, well developed and accepted by all actors; therefore, academic achievments reflected in the rank of the educational institution strongly influence allocation in the labour market and subsequently the careers of employees. According to these widespread considerations, schools with a partly vocational curriculum and less emphasis on general courses consequently rank low within the educational system and career prospects of its graduates are gloomy. However, in this article some empirical evidence is presented that enterprises in manufacturing industries regard vocational skills highly, hiring and promoting graduates of vocational high schools, prefering them to-those from general high schools. The authors conclude that conventional theory tends to typify and simplify the relation of education and employment in Japan. An integration of such deviations and differentiations into theory is-needed. (DIPF/ Orig.)
Keywords: S System beruflicher Bildung; G 1.3.3.1 Qualifikationsverwertung; G 1.2 Arbeitsmarkt; T 3.4 Befragung; I 2.3.4 Asien; Bildungssystem; Berufsausbildung; Berufliche Weiterbildung; Qualifizierung; Qualifikationsverwertung; Arbeitsorganisation; Arbeitsmarkt; Lebenslanges Lernen; Empirische Untersuchung; Japan